2008
DOI: 10.1111/j.1540-6261.2008.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Stock Returns and Volatility: Pricing the Short‐Run and Long‐Run Components of Market Risk

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
104
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(119 citation statements)
references
References 96 publications
15
104
0
Order By: Relevance
“…These results suggest that the impact of the business cycle on asset returns in our three component beta model is primarily captured through the medium-and long-run beta components. This is in line with Adrian and Rosenberg (2008) who also find that the business cycle is correlated with a long-run component of risk in their factor pricing model containing a short-and long-run volatility component. Overall, these results suggest that the more immediate changes in risk such as changes in portfolio characteristics are captured in the short-run beta component while the medium-and long-run beta components capture more slowly changing risk which we find to be correlated with the business cycle.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results suggest that the impact of the business cycle on asset returns in our three component beta model is primarily captured through the medium-and long-run beta components. This is in line with Adrian and Rosenberg (2008) who also find that the business cycle is correlated with a long-run component of risk in their factor pricing model containing a short-and long-run volatility component. Overall, these results suggest that the more immediate changes in risk such as changes in portfolio characteristics are captured in the short-run beta component while the medium-and long-run beta components capture more slowly changing risk which we find to be correlated with the business cycle.…”
Section: Introductionsupporting
confidence: 76%
“…2 As we discuss below, we also take a closer look at the pricing errors for individual assets, which allow us to analyze which assets are mispriced across different models. The second and third metrics are the sum of square pricing errors (SSPE) and root mean square pricing errors (RMSPE) (see Adrian and Rosenberg (2008)):…”
Section: Performance Measuresmentioning
confidence: 99%
“…Importantly, however, Bollerslev et al (2014) and (2009) Indeed, Bollerslev and Zhou (2006) showed that the volatility series "exhibit pronounced own temporal dependencies" and Adrian and Rosenberg (2008) showed that investors require compensation when holding assets that depreciate as volatility rises. 4…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…3 However, 1 See, for example, Garcia et al (2009), Jones (2003), Li and Zhang (2013), and the literature cited therein. 2 See also Adrian and Rosenberg (2008), Bates (2000Bates ( , 2012, Campbell et al (2012), Chernov et al (2003), Christoffersen et al (2009), Christoffersen, Dorion, Jacobs andWang (2010), Egloff et al (2010), and Lux and Kaizoji (2007).…”
Section: Introductionmentioning
confidence: 99%